Tinjauan Pelepasan Informasi Medis Kepada Pihak Ketiga di Rumah Sakit Setia Mitra - Lidia Kanaf; Hudiyati Agustini; Tite Kabul (APIKES Bhumi Husada Jakarta, 2017)
ABSTRACT The health ministry`s regulation number 269 2008 on Medical Record, stating that Information about identity, diagnosis, history of disease, history of examination and history of treatment can be opened in accordance with the provisions. Based on the observations made, there is no official who handles the release of medical information and there is no specific responsibility for handling it, so the problem is: how the implementation of the release of medical information to the third party at Setia Mitra Hospital Jakarta ?. The purpose of this research is to know the process of releasing medical information to third party at Setia Mitra Hospital. This research was conducted by using descriptive design. Conclusion, Setia Mitra Hospital already has a policy on the release of medical information in the form of standard operational procedures and general consent form. However, there is no specific regulatory policy regarding the release of medical information. 73.7% of Medical Record Officers understand the importance of SPO (standard operational procedures) made and adhered to. In practice most of them are in accordance with the procedures and theories of health law, while not yet appropriate is the recording and the use of book of expedition and the absence of deadline for the use of written permission from patients. Keywords: the release of medical information